Suicide and deliberate self-harm in Oxford University students over a 30-year period - Hawton, K; Bergen, H; Mahadevan, S; Casey, D; Simkin, S (2012)
Purpose To determine whether rates of suicide and self- harm in university students differ from those in other young people. Methods We obtained information on Oxford University students who died by suicide or presented to hospital following deliberate self-harm (DSH) between 1976 and 2006 from official records and a General Hospital monitoring system in Oxford. Rates of suicide and self-harm in the students and in other young people in the general population were calculated from university, local and national population figures. Results Forty-eight Oxford University students (32 males and 16 females) died by suicide. Most (N = 42) were aged 18-25 years. The suicide rate did not differ from that of other people in this age group in England and Wales (SMR 105.4; 95% CI 75.2, 143.4). There was evidence of clustering of methods of suicide over time. During the same period, 602 students (383 females and 219 males) presented to the General Hospital following DSH. Most (90.7%) were aged 15-24 years, in which age group rates of DSH (per 100,000) during term-time were lower than in other young people in Oxford City (females: 206.5 vs. 285.6, z =-5.03, p < 0.001; males: 75.9 vs. 111.2, z =- 4.35; p < 0.001). There was an excess of student DSH episodes in the main exam term. Conclusions Contrary to earlier findings and popular belief, suicide rates in Oxford University students do not differ from those in other young people. Rates of DSH are significantly lower than in other young people. Risk of DSH may increase around the time of examinations. © Springer-Verlag 2010.